PENERAPAN IPTEKS PERHITUNGAN KEWARISAN MENURUT HUKUM ISLAM - Tri Yanuaria; Kadir Katjong (LPPM Uncen, 2020)
This service was carried out with the title of Applied of Science and Technology of on Calculation of Inheritance in islamic law, which was held on Saturday 31 August 2018 in Masjid Takul Masjid Baitul Makmur, activities to be carried out to partners due to a case from partners regarding the understanding of inheritance according to Islamic law so that with the expertise possessed by servants can implement the science and technology. The implementation of this service was carried out by applying science and technology and mentoring technical guidance to partners in calculating the distribution of inheritance according to Islamic inheritance law. The outcome of this service is the increase in partner knowledge about the procedures and procedures for distributing inheritance according to Islamic inheritance law.Keywords: inheritance, inheritance law, islamic law, law.